Pengembangan Algoritma untuk Menganalisis Frekuensi Pribadi Poros dengan Rotor Ganda - Amir Zaki Mubarak (Jurnal Teknik Mesin Unsyiah, 2012)
Vibration analysis is very essential to be considered in designing a rotor shaft. By the development of computer technology, the vibration analysis of the rotor shaft can be easily performed by numeric method. The objective of this research is to develop an algorithm to determine the natural frequency of a rotor shaft of a dual rotor system. The equation of motion of the system is derived from the kinetic and potential energy. By applying Lagrange’s equation and converting them into matrix form, the equations can be easily solved numerically. Through this approximation is developed computer program. The model is a rotor system built of a rotor shaft and two disks. The rotor shaft is numerically divided into several line elements. From the global matrices of the elements, it is resolved the eigen values of the system which are then converted into the natural frequencies. The validation of the program result with analytical calculation shows a very close result.